Method for forming high-binding-force coating on surface of metal substrate and application

By polishing, sandblasting and electrostatic spraying of the metal matrix, forming a polymer coating, the problem of insufficient bonding between the metal matrix and the polymer coating is solved, and the scratch resistance of the polymer coating and the metal matrix are significantly improved. The fatigue resistance extends the service life of the equipment.

CN119158763APending Publication Date: 2024-12-20TSINGHUA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411282016.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The lack of bonding between the metal matrix and the polymer coating leads to the easy peeling and damage of the polymer coating, affecting the service life of the equipment.

Method used

The polymer coating is formed by grinding and polishing the metal substrate, sandblasting strengthening treatment and electrostatic spraying, thereby enhancing the bonding of the polymer coating and the metal substrate. The specific steps include grinding and polishing using different mesh numbers of sandpaper, sandblasting reinforcement treatment with different types and particle sizes, and spraying the polymer coating through electrostatic spraying technology to optimize the spraying parameters to improve binding force.

Benefits of technology

It significantly enhances the scratch resistance of the polymer coating and the fatigue resistance of the metal matrix, avoids peeling and damage of the coating, improves the bonding force between the metal and polymer interface, and extends the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005042357490000051
    Figure BDA0005042357490000051
  • Figure HDA0005042357570000011
    Figure HDA0005042357570000011
  • Figure HDA0005042357570000012
    Figure HDA0005042357570000012
Patent Text Reader

Abstract

The invention provides a method for forming a high-binding-force coating on the surface of a metal substrate and application. The method comprises the following steps: (1) carrying out grinding and polishing treatment on a metal matrix; (2) sand blasting strengthening treatment; and (3) forming a polymer coating on the surface of the metal matrix through electrostatic spraying. According to the method, the bonding property between the polymer coating and the metal matrix is remarkably improved, the scratch resistance of the polymer coating is remarkably enhanced, and the situation that the polymer coating is extremely prone to stripping and damage in the assembling and testing process of complex workpieces is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material technology, and specifically relates to a method and application of forming a strong bonding coating on the surface of a metal substrate. Background Art

[0002] Metal materials and other types of materials will experience severe adhesion, friction and wear during long-term testing or service, which will affect the service life of the equipment. Resin-based composite materials are a multiphase material composed of a resin matrix and various reinforcing materials and other fillers. Their performance is superior to that of a single material, effectively improving the shortcomings of a single resin matrix such as poor mechanical properties. They are currently a type of composite material with relatively mature technology and the most widely used. However, during the application process, polymer composite coatings have the problem of weak bonding with metal matrix materials, are very easy to peel off and damage, and cannot achieve the protective effect. Therefore, the bonding between the interface of metal materials and polymer coatings is one of the problems that need to be solved urgently. Summary of the invention

[0003] In order to solve the above problems, the purpose of the present invention is to provide a method and application for forming a strong bonding coating on the surface of a metal substrate, which significantly improves the bonding between the polymer coating and the metal substrate, significantly enhances the scratch resistance of the polymer coating, and avoids the situation where the polymer coating is easily peeled off and damaged during the assembly and testing of complex workpieces.

[0004] In order to achieve the above object, the present invention provides a method for forming a strong bonding coating on the surface of a metal substrate, which comprises the following steps:

[0005] (1) Grinding and polishing the metal substrate;

[0006] (2) Sandblasting treatment;

[0007] (3) A polymer coating is formed on the surface of the metal substrate through electrostatic spraying.

[0008] According to a specific embodiment of the present invention, preferably, the mesh number of the sandpaper used for grinding and polishing treatment includes one or a combination of two or more of 300#, 600#, 800#, 1200#, 1500#, 2000#, 2400#, 3000#, and 4000#.

[0009] According to a specific embodiment of the present invention, preferably, the sandblasting particles used in the sandblasting strengthening treatment include one or a combination of two or more of copper ore sand, quartz sand, corundum, iron sand and Hainan sand.

[0010] According to a specific embodiment of the present invention, preferably, the particle size of the sandblasting particles used in the sandblasting strengthening treatment is 10-2000 μm, more preferably 50-500 μm. Controlling the particle size of the sandblasting particles within the above range will not affect the surface smoothness of the coating, but can significantly improve the bonding between the metal and the coating.

[0011] According to a specific embodiment of the present invention, preferably, the mesh size of the sandblasting particles used in the sandblasting strengthening treatment is 46#.

[0012] According to a specific embodiment of the present invention, preferably, the pressure of the sandblasting treatment is 20-150Pa, more preferably 50-120Pa.

[0013] According to a specific embodiment of the present invention, preferably, the angle of the sandblasting strengthening treatment is 15°-90°.

[0014] According to a specific embodiment of the present invention, preferably, the distance of the sandblasting strengthening treatment is 80-300 mm.

[0015] According to a specific embodiment of the present invention, preferably, the voltage used for the electrostatic spraying is 50-120V, for example, 50V, 60V, 70V, 80V, 90V, 100V, 110V, 120V.

[0016] According to a specific embodiment of the present invention, preferably, the current used for the electrostatic spraying is 50-100A, for example, 50A, 60A, 70A, 80A, 90A, 100A.

[0017] According to a specific embodiment of the present invention, preferably, the electrostatic spraying adopts a spraying distance of 100-400 mm, for example, 100 mm, 150 mm, 200 mm, 250 mm, 300 mm, 350 mm, 400 mm.

[0018] According to a specific embodiment of the present invention, preferably, the air supply pressure used in the electrostatic spraying is 5-20Pa, for example, 5Pa, 6Pa, 7Pa, 8Pa, 9Pa, 10Pa, 11Pa, 12Pa, 13Pa, 14Pa, 15Pa, 16Pa, 17Pa, 18Pa, 19Pa, 20Pa.

[0019] According to a specific embodiment of the present invention, preferably, the thickness of the polymer coating is 93-124 μm.

[0020] According to a specific embodiment of the present invention, preferably, the material of the polymer coating, calculated by mass percentage, comprises: 50-86% polyester resin, 10-30% titanium dioxide, 1-5% curing agent, 1-5% accelerator, 1-5% benzoin, and 1-35% leveling agent, wherein the curing agent can be selected as cyclohexanone dibutyl peroxide paste, the accelerator can be selected as calcium ethylhexanoate, and the leveling agent can be selected as diacetone alcohol.

[0021] According to a specific embodiment of the present invention, preferably, the material of the polymer coating is prepared by the following steps:

[0022] (1) Mixing raw materials for polymer coating;

[0023] (2) melt extrusion blending and cooling;

[0024] (3) crushing, classifying and screening to obtain the polymer coating material.

[0025] According to a specific embodiment of the present invention, preferably, in step (2), the melting temperature is 80-300°C; more preferably, in step (3), the particle size of the material of the obtained polymer coating is 1-50 μm, more preferably 5-15 μm.

[0026] According to a specific embodiment of the present invention, the above method comprises the following specific steps:

[0027] First, the metal material substrate is ground and polished by a grinding and polishing machine; then, it is sandblasted and strengthened by a dry box sandblasting machine, wherein the sandblasting particles are of different types and mesh sizes (i.e., particle sizes), and the appropriate sandblasting pressure, sandblasting angle, and sandblasting distance are set; then, an electrostatic spraying method is used, and a layer of polymer coating is sprayed by setting appropriate current voltage, spraying distance, and air supply pressure.

[0028] According to a specific embodiment of the present invention, preferably, before the sandblasting treatment, the metal substrate is subjected to one or a combination of two or more of alkylation treatment, phosphating treatment and pickling.

[0029] The invention also provides application of the method in coating the surface of fasteners and bushing samples with a polymer coating.

[0030] The method of the present invention, without changing the mechanical and tribological properties of the polymer coating, significantly improves the bonding between the polymer coating and the metal substrate by sandblasting, significantly enhances the scratch resistance of the polymer coating, and avoids the situation that the polymer coating is very easy to peel off and be damaged during the assembly and testing of complex workpieces. The sandblasting in the method of the present invention introduces residual compressive stress to improve the fatigue resistance of the metal substrate. The applied coating plays a role in turning the full slip zone and the mixed zone in the micro-motion operating diagram to the partial slip zone, plays a role in regional transfer, and prevents the occurrence of micro-motion phenomenon. Therefore, the residual compressive stress introduced by sandblasting and the anti-micro-motion of the coating jointly play a role in preventing micro-motion fatigue wear. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of metal material, sandblasting layer and polymer coating;

[0032] Figure 2 Actual photo of polymer coating without sandblasting;

[0033] Figure 3 Actual photo of polymer coating after sandblasting;

[0034] Figure 4 Bonding strength data after sandblasting with different mesh sizes. DETAILED DESCRIPTION

[0035] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0036] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. The equipment used or the manufacturer is not specified are all conventional products that can be purchased from the market.

[0037] The polymer coating materials used in the following examples and comparative examples are prepared by the following steps:

[0038] (1) First, 60 g of polyester resin, 15 g of titanium dioxide, 25 g of dye, 1.8 g of curing agent (cyclohexanone dibutyl peroxide paste), 1.2 g of accelerator (calcium ethylhexanoate), 1.5 g of benzoin, and 1.5 g of leveling agent (diacetone alcohol) were thoroughly mixed;

[0039] (2) extruding the mixed material in sheet form through a twin-screw extruder at a melting temperature of 80° C. and then cooling the mixed material to room temperature;

[0040] (3) The obtained tablet composite material (flaky mixed material) is crushed and graded and sieved by an ultrafine pulverizer, and powder with an average particle size of 10 μm is selected for spraying.

[0041] Example 1

[0042] This embodiment provides a method for forming a strong bonding coating on the surface of a metal substrate, which includes the following steps:

[0043] First, 800#, 1200#, and 2000# grit sandpapers were used to grind and polish the metal material substrate (GCr15, the same below) through a grinding and polishing machine to facilitate subsequent sandblasting. Then, a dry box sandblasting machine was used for sandblasting reinforcement. The sandblasting particles used were 46# corundum particles, the sandblasting pressure was 60Pa, the angle was 30°, the distance was 100mm, and the sandblasting treatment lasted for 5 minutes (the same below). Then, an electrostatic spraying method was used to set a suitable current of 70A, a voltage of 100V, a spraying distance of 200mm, and an air supply pressure of 10Pa to spray a layer of polymer coating, and the coating thickness was 93-124 microns, the same below. The appearance of the polymer coating is as follows: Figure 3 The schematic structure of the metal material, sandblasting layer and polymer coating is shown in Figure 1 Finally, the bonding strength between the polymer coating and the metal material was tested by a nano scratch tester (2N / min) at different blasting grits. The bonding strength between the polymer coating and the metal substrate of Example 1 was measured to be 20.82N, and the results are shown in Table 1.

[0044] Example 2

[0045] This embodiment provides a method for forming a strong bonding coating on the surface of a metal substrate, which includes the following steps:

[0046] First, 800#, 1200#, and 2000# mesh sandpapers are selected, and the metal material (GCr15) substrate is polished and polished by a grinding and polishing machine to facilitate subsequent sandblasting; then, a dry box sandblasting machine is used for sandblasting strengthening, and the sandblasting particles are 80# diamond particles, the sandblasting pressure is 60Pa, the angle is 30°, and the distance is 100mm; then, an electrostatic spraying method is used, and a suitable current of 70A, a voltage of 100V, a spraying distance of 200mm, and an air supply pressure of 10Pa are set to spray a layer of polymer coating; finally, a nano scratch instrument is used to detect the bonding force between the polymer coating and the metal material when different sandblasting meshes are detected. The bonding force between the polymer coating and the metal substrate of Example 2 is measured to be 8.59N, and the results are shown in Table 1.

[0047] Example 3

[0048] This embodiment provides a method for forming a strong bonding coating on the surface of a metal substrate, which includes the following steps:

[0049] First, 800#, 1200#, and 2000# mesh sandpapers are selected, and the metal material substrate is polished and polished by a grinding and polishing machine to facilitate subsequent sandblasting; then, a dry box sandblasting machine is used for sandblasting strengthening, and the sandblasting particles are 120# diamond particles, the sandblasting pressure is 60Pa, the angle is 30°, and the distance is 100mm; then, an electrostatic spraying method is used, and a suitable current of 70A, a voltage of 100V, a spraying distance of 200mm, and an air supply pressure of 10Pa are set to spray a layer of polymer coating; finally, a nano scratch tester is used to detect the bonding force between the polymer coating and the metal material at different sandblasting meshes. The bonding force between the polymer coating and the metal substrate of Example 3 is measured to be 3.79N, and the results are shown in Table 1.

[0050] Comparative Example 1

[0051] This comparative example provides a method for spraying a polymer coating on a metal substrate, which comprises the following steps:

[0052] First, use 800#, 1200#, 2000# sandpaper to grind and polish the metal material substrate with a grinding and polishing machine; do not perform sandblasting; then use the electrostatic spraying method to set a suitable current of 70A, voltage of 100V, spraying distance of 200mm and air supply pressure of 10Pa to spray a layer of polymer coating. The appearance of the polymer coating is as follows: Figure 2 As shown; Finally, the bonding strength between the polymer coating and the metal material was tested by a nano scratch tester at different grits. The bonding strength between the comparative polymer coating and the metal substrate was 1.59N, and the results are shown in Table 1. The bonding strength data after grit blasting at different grits are shown in Figure 4 .

[0053] Table 1 Binding strength test results

[0054]

[0055] Comparative Example 2

[0056] This comparative example provides a method for spraying a polymer coating on a metal substrate, and the steps are the same as those in Example 1, except that the blasting angle in this comparative example is 10°. The bonding force test result is 15.69N.

[0057] Comparative Example 3

[0058] This comparative example provides a method for spraying a polymer coating on a metal substrate, and the steps are the same as those of Example 3, except that this comparative example uses 120# aluminum oxide, and the bonding strength test result is as follows: 2.34N.

[0059] Mechanical properties test:

[0060] A hardness test was performed on the above-mentioned comparative examples and embodiments using a Rockwell hardness tester with a steel ball indenter. The test results are as follows, showing that the hardnesses of comparative examples 1, 2 and 3 are 75.3 HRB, 75.8 HRB and 75.6 HRB, respectively, and the hardnesses of embodiments 1, 2 and 3 are 76.7 HRB, 76.6 HRB and 76.1 HRB, respectively, indicating that sandblasting, changes in the sandblasting process and changes in the sandblasting particles do not significantly affect the hardness of the samples.

[0061] Tribological performance test:

[0062] The friction coefficients of the comparative examples and embodiments were measured using a friction and wear tester SRV-IV. The test results are as follows: the friction coefficients of comparative examples 1, 2 and 3 are 0.75, 0.73 and 0.76, respectively; the friction coefficients of embodiments 1, 2 and 3 are 0.76, 0.77 and 0.75, respectively, indicating that sandblasting, changes in the sandblasting process and changes in the sandblasting particles do not significantly affect the tribological properties of the samples.

[0063] In the description of this specification, the description with reference to the term "embodiment" or the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0064] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for forming a strong bonding coating on the surface of a metal substrate, comprising the following steps: (1) Grinding and polishing the metal substrate; (2) Sandblasting treatment; (3) A polymer coating is formed on the surface of the metal substrate through electrostatic spraying.

2. The method according to claim 1, wherein: The mesh numbers of sandpaper used for grinding and polishing include one or a combination of two or more of 300#, 600#, 800#, 1200#, 1500#, 2000#, 2400#, 3000#, and 4000#.

3. The method according to claim 1, wherein: The sandblasting particles used in the sandblasting strengthening treatment include one or a combination of two or more of copper ore sand, quartz sand, corundum, iron sand and Hainan sand.

4. The method according to claim 1, wherein: The particle size of the sandblasting particles used in the sandblasting strengthening treatment is 10-2000 μm, preferably 50-500 μm; Preferably, the mesh size of the sandblasting particles used in the sandblasting strengthening treatment is 46#.

5. The method according to claim 1, wherein: The pressure of the sandblasting strengthening treatment is 20-150Pa, preferably 50-120Pa.

6. The method according to claim 1, wherein: The angle of the sandblasting strengthening treatment is 15°-90°; Preferably, the distance of the sandblasting strengthening treatment is 80-300 mm.

7. The method according to claim 1, wherein: The voltage used for the electrostatic spraying is 50-120V; Preferably, the current used in the electrostatic spraying is 50-100A; Preferably, the electrostatic spraying adopts a spraying distance of 100-400 mm; Preferably, the air supply pressure used in the electrostatic spraying is 5-20Pa; Preferably, the polymer coating has a thickness of 93-124 μm.

8. The method according to claim 1, wherein: The polymer coating material, calculated by mass percentage, comprises: 50-86% polyester resin, 10-30% titanium dioxide, 1-5% curing agent, 1-5% accelerator, 1-5% benzoin, and 1-35% leveling agent.

9. The method according to claim 1, wherein: Before the sandblasting treatment, the metal substrate is subjected to one or a combination of two or more of alkylation treatment, phosphating treatment and pickling.

10. Use of the method according to any one of claims 1 to 9 in coating a polymer coating on the surface of a fastener or bushing specimen.

Citation Information

Patent Citations

  • Composite strengthening method of metal material and application of composite strengthening method

    CN118048513A

  • Self-lubricating coating, preparation method thereof and method for forming self-lubricating coating

    CN119101425A